Microwave Characterization of Metal Powder in Additive Manufacturing (AM) - Joseph Filbert; Aaron Barvincak; Mohammad Tayeb Al Qaseer; Reza Zoughi (IEEE Open Journal of Instrumentation and Measurement)
Common additive manufacturing (AM) methods use metal powder feedstock. The properties of the metal powder, such as particle size distribution (PSD), morphology, and presence of surface oxides or other contaminants, significantly impact the quality of the built part. Microwave materials characterization techniques potentially offer effective means by which to evaluate such metal properties. To assess sensitivity of microwave signals to the properties of metal powder used in AM, different types of metal powder were incorporated into resin composite samples, whose dielectric and magnetic properties were then measured using the well-known completely filled-waveguide technique at the Ka-band (26.5–40 GHz) and V-band (50–67 GHz). These measurements revealed that microwave signals are sensitive to small (~0.5%) changes in the metal powder volume fraction. It was also found that the resin powder composites exhibited diamagnetic properties and could be accurately modeled using effective media theories which consider both the dielectric and magnetic properties. The findings open the door for future investigations by which optimized techniques can be devised to do the same in an in-line manner during the AM process.